Algorithms for noise reduction in signals : theory and practical examples based on statistical and convolutional analysis /: theory and practical examples based on statistical and convolutional analysis. ([2022]) - Iglesias Martínez, Miguel Enrique; García March, Miguel Ángel; Milián Enrique, Carles; Fernández de Córdoba, Pedro
No abstract available